Anchorless Onlay Dynamic Anterior Stabilization of the Shoulder Using a Guided Posterior Double Endobutton Fixation - Maia Dias, C (2024)
The treatment of shoulder instability in the presence of a subcritical glenoid defect poses challenges, as simple Bankart seems insufficient, and the Latarjet procedure may be excessive. Recently, a dynamic anterior stabilization technique involving anterior transposition of the long head of the biceps (LHB) through a subscapularis split was described for that purpose. Previously published results demonstrated good short-term results, but several technical pitfalls have also been mentioned. We describe an onlay, anchorless, and intra-articular knotless method of fixing the LHB into the anterior glenoid that provides the important stabilizing "sling effect" of the dynamic anterior stabilization while avoiding some of the pitfalls described by other techniques.